2020
DOI: 10.51978/agro.v9i1.97
|View full text |Cite
|
Sign up to set email alerts
|

Inventarisasi Serangga Pada Tanaman Refugia Di Lahan Teaching Farm, Buludua

Abstract: Tanaman refugia mempunyai potensi menyokong mekanisme sistem yang meliputi perbaikan ketersediaan makanan alternatif seperti nektar, serbuk sari, dan embun madu; menyediakan tempat berlindung atau iklim mikro yang digunakan serangga predator untuk bertahan melalui pergantian musim atau berlindung dari faktor-faktor ekstremitas lingkungan atau pestisida; dan menyediakan habitat untuk inang atau mangsa alternative. Pengamatan dilakukan di lahan teaching farm, Buludua bertujuan untuk mengidentifikasi jenis-jenis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…According to Allifah et al (2019), some studies mention the types of ornamental plants that have the potential as refugia are sunflowers (Helianthus annuus), paper flowers (Zinnia peruviana), kenikir (Cosmos caudatus), cempasuchil (Tagetes erecta), and several other types of flowers. Some weeds derived from the family Asteraceae such as billygoat-weed (Ageratum conyzoides) and cobblers pegs (Bidens pilosa L.) can also be used as refugia plants (Muliani et al, 2020). Widiastuti (2000) reported that the insect family Coccinellidae prefers wild plants from the family Asteraceae, such as Eupatorium and Bidens.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…According to Allifah et al (2019), some studies mention the types of ornamental plants that have the potential as refugia are sunflowers (Helianthus annuus), paper flowers (Zinnia peruviana), kenikir (Cosmos caudatus), cempasuchil (Tagetes erecta), and several other types of flowers. Some weeds derived from the family Asteraceae such as billygoat-weed (Ageratum conyzoides) and cobblers pegs (Bidens pilosa L.) can also be used as refugia plants (Muliani et al, 2020). Widiastuti (2000) reported that the insect family Coccinellidae prefers wild plants from the family Asteraceae, such as Eupatorium and Bidens.…”
Section: Articlementioning
confidence: 99%
“…Refugia plants are generally only known as flowering plants in the cultivation plant area. However, according to experts, the definition of refugia plants are some types of plants that can provide shelter, feed sources, or other resources for natural enemies such as predators and parasitoids (Muliani et al, 2020). Refugia plants are generally planted on the mound's edge or outside the plant in a long and striking flowering.…”
mentioning
confidence: 99%
“…Potensi dari refugia yaitu menyediakan nektar, serbuk sari, dan embun madu. Sebagai mikrohabitat sehingga predator dan parasitoid dapat berlindung dari faktor-faktor ekstremitas lingkungan atau pada saat pengaplikasian jenis pestisida (Muliani et al, 2020).…”
Section: Pendahuluanunclassified